Primary Vaginal Carcinoma in Prolapsed Uterus (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Not available DOI: http://dx.doi.org/10.3329/jbcps.v30i3.12471 J Bangladesh Coll Phys Surg 2012; 30: 181-182